Enhancing Student’s Pronunciation Capability Using Microsoft Speech Recognition Engine - Bahruddin (Proceeding International Conference on Education, 2023)
Pronunciation is crucial for language learners as it directly influences their communication skills and overall language proficiency. This paper explores the potential of leveraging Microsoft's Speech Recognition Engine (MSRE) as a tool to enhance students' pronunciation capabilities. The study employs a mixed-methods approach, combining quantitative assessments and qualitative observations to evaluate the impact of using MSRE in a language learning environment. The methodology involves pre-test and post-test, where students' pronunciation proficiency is measured before and after incorporating MSRE. The real-time feedback provided by the speech-recognition engine helps learners identify and rectify pronunciation errors, promoting self-correction and self-directed learning.  This study contributes to the growing body of research on technology-enhanced language learning, specifically in the context of pronunciation improvement. The findings highlight the potential of MSRE as a valuable addition to language classrooms, emphasizing its role in fostering autonomous language learning and empowering students to take ownership of their language development.